Research issues in systems analysis and design, databases and software development - Siau, Keng 1964- (Advanced topics in database research series., 2007)
Designed to provide understanding of the capabilities and features of new ideas and concepts in the information systems development, database, and forthcoming technologies. It provides a representation of top notch research in all areas of systems analysis and design and database.